"The Tube is Flickering Now": Aesthetics of Authenticity in Good Night, and Good Luck - Sina Nitzsche (Current Objectives of Postgraduate American Studies)
The article examines the Clooney/Heslov/Soderbergh production Good Night, and Good Luck“ (2005). Its unusual visual style (cinematography, mise-en-scène, etc.) enables an immediate aesthetic viewing experience of Cold War America. Drawing on Fluck's discussion about aesthetics and its socio-cultural function, the "docu-drama" (Doherty 53), while referring to the era of McCarthyism, serves as an instance of articulation for the dissatisfaction with contemporary American politics.